2015
DOI: 10.1103/physrevlett.115.258302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Alignment of Block Copolymer Microdomains by Intrinsic Chain Anisotropy

Abstract: We examine the role of intrinsic chain susceptibility anisotropy in magnetic field directed selfassembly of a block copolymer using in situ X-ray scattering. Alignment of a lamellar mesophase is observed on cooling across the disorder-order transition with the resulting orientational order inversely proportional to the cooling rate. We discuss the origin of the susceptibility anisotropy, ∆χ, that drives alignment, and calculate its magnitude using coarse-grained molecular dynamics to sample conformations of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 40 publications
4
49
0
2
Order By: Relevance
“…These values represent the characteristic dimensions for grains which at steady state would reproduce the field-dependent orientation distributions observed experimentally. This steady-state assumption and the fact that the degree of alignment observed experimentally is dependent on the cooling rate suggests that the inferred grain sizes underestimate the actual grain sizes to some degree, as observed in prior work (16).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…These values represent the characteristic dimensions for grains which at steady state would reproduce the field-dependent orientation distributions observed experimentally. This steady-state assumption and the fact that the degree of alignment observed experimentally is dependent on the cooling rate suggests that the inferred grain sizes underestimate the actual grain sizes to some degree, as observed in prior work (16).…”
Section: Resultssupporting
confidence: 60%
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The LC mesophase within the BCP superstructure provides a ≈100-to 1,000-fold increase in ∆χ relative to non-LC BCPs. Conversely, recent work has demonstrated that the intrinsic susceptibility anisotropy (∆χ ≈ 10 −8 ) of non-LC BCPs can be sufficient to provide strong alignment at field strengths of 5-6 T, due to the large grain sizes produced in certain low-molecular-weight BCPs, with ξ > 1 µm (16,17). The aforementioned cases contrast sharply with smallmolecule LCs where alignment can be driven readily at fields below 1 T (18)(19)(20).…”
Section: Magnetic-field Dsa Of Bcpsmentioning
confidence: 98%
“…Rokhlenko et al, using transmission electron microscopy (TEM), demonstrated that magnetic field produces alignment of polymer microdomains which are sensitive to temperature and magnetic field strength. 42 Their work, however, involved high magnetic fields up to 6 T, which is significantly higher than the 0.35 T B-field used in the MRIgRT system used in our work. Due to the presence of magnetic field during irradiation, the film response may change due to the formation of polymer microdomains 42 and production of longer polymer chains.…”
Section: Discussionmentioning
confidence: 81%
“…However, for most applications precise control over orientation with a minimum amount of defects is favorable. Different techniques have been established to obtain highly aligned samples from block copolymers, for example the application of external stimuli such as magnetic 13,14 or electric fields, 15 shear force, 16,17 temperature gradients, 18 and patterned substrates [19][20][21] have been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%